APPLICATION OF DEMPSTER SHAFER FOR CANARY DISEASE DIAGNOSIS AT IN LIVESTOCK AND ANIMAL HEALTH SERVICE OF ASAHAN REGENCY - Reza Arif Sya’bana; Dewi Anggraeni; Hommy Dorthy Ellyany Sinaga (Informatika, Universitas Jenderal Soedirman, 2022)
Canaries are birds that are in great demand by hobbyists and breeders, especially local canaries and imported canaries. The advantages of imported canaries have an ideal body posture and also thick fur. However, where there are few problems with imported canaries, especially the sound that tends to be less noisy and the duration of the tone is not too long and canaries can be cultivated because they have a high economic value. Canaries are also very easily infected with diseases, infections that can attack these canaries, such as diseases caused by polioma infections or also disorders from parasites and bacterial contamination of the digestive organs. To overcome this problem, an expert system was created to diagnose diseases in canaries using the Dempster Shafer method with the PHP programming language and MySQL database. This expert system application is designed using the Dempster Shafer method based on subjective possibilities and rules in combining degrees of confidence based on the evidence obtained. This theory has several characteristics that are intuitively in accordance with the way of thinking of an expert, but a strong mathematical basis. With this application, it is hoped that it will make it easier for the hobbyist/breeder to find out the disease he is suffering from and find out what percentage of the disease he suffers, so that the hobbyist/breeder can take immediate action.